2013
DOI: 10.1021/es401730s
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Electrochemically Generated Ferrous Ions from an Iron Cathode for Pd-Catalytic Transformation of MTBE in Groundwater

Abstract: An effective approach is developed to regulate the generation of Fe 2+ from an iron cathode in a three-electrode system. The Fe 2+ is then used for the Pd-catalytic transformation of methyl tert-butyl ether (MTBE) in simulated groundwater. Under conditions of pH 3, a total current of 50 mA, and 1 g/L Pd/Al 2 O 3 , 20 mg/L MTBE was completely transformed within 60 min in an undivided electrolytic cell using the iron cathode, with 14 mg/L of accumulated Fe 2+. Fe 2+ accumulation follows pseudo-first-order kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 59 publications
3
27
0
Order By: Relevance
“…The pseudo-first-order kinetics rate constant for toluene transformation increased from 0.010 min −1 in the absence of HA to 0.015 min −1 in the presence of 10 mg/L HA ( Table 1 ). The rate constants normalized by Pd concentration (0.05 gPd/L) is 0.2 and 0.3 L/gPd/min in the absence and presence of 10 mg/L HA, respectively, which is in the same level as that reported by our recent work 14 and one order of magnitude smaller than that reported by Lowry and Reinhard using Pd and H 2 for TCE hydrodechlorination 24 . The solution pH increased from 3.0 to 3.4 during the course of experiments in the absence and presence of 10 mg/L HA, which is attributed to the consumption of H + by chemical corrosion of the iron cathode ( eq.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…The pseudo-first-order kinetics rate constant for toluene transformation increased from 0.010 min −1 in the absence of HA to 0.015 min −1 in the presence of 10 mg/L HA ( Table 1 ). The rate constants normalized by Pd concentration (0.05 gPd/L) is 0.2 and 0.3 L/gPd/min in the absence and presence of 10 mg/L HA, respectively, which is in the same level as that reported by our recent work 14 and one order of magnitude smaller than that reported by Lowry and Reinhard using Pd and H 2 for TCE hydrodechlorination 24 . The solution pH increased from 3.0 to 3.4 during the course of experiments in the absence and presence of 10 mg/L HA, which is attributed to the consumption of H + by chemical corrosion of the iron cathode ( eq.…”
Section: Resultssupporting
confidence: 74%
“…Moreover, regarding the supply of Fe(II), sacrificial iron anode can be effective but it may produces excess amount of iron sludge 11 13 . To overcome the limitation of applying E-Fenton process in subsurface remediation, we have recently developed a novel Pd-based E-Fenton process 14 . As illustrated in Figure S1 , the process was performed in a modified three-electrode system, which contains a mixed metal oxides (MMO) anode, an iron cathode, and another MMO cathode (the composition was the same as MMO anode).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Without current applied to the iron anode (20/0), TCE was only reduced by 25.3% within 4 h; when 5 mA current was applied to the iron anode (15/5), the removal increased to 66.0%; and when the applied current further increased, the removal efficiency stabilized at about 79.5%. Previous studies showed that TCE degradation shifted from reductive dechlorination in the absence of Fe(II) to OH oxidation in the presence of Fe(II) under acidic conditions, but OH oxidation was negligible at the pH above 6 because the generation of H 2 O 2 was limited and most Fe(II) was precipitated (Liao et al, 2013;Yuan et al, 2013aYuan et al, , 2012. Therefore, hydrodechlorination mechanism predominated for TCE degradation under the neutral circumstance in this work.…”
Section: Feasibility Tests In the Labmentioning
confidence: 59%